2019
DOI: 10.1108/ijlls-04-2019-0031
|View full text |Cite
|
Sign up to set email alerts
|

Lesson Study effectiveness for teachers’ professional learning: a best evidence synthesis

Abstract: Purpose The purpose of this paper is to gather evidence for the effectiveness of Lesson Study (LS) for teachers’ professional learning. Design/methodology/approach A systematic review of relevant papers published between January 2010 and April 2018 was performed. To accomplish the best evidence synthesis, relevant studies were selected based upon well-chosen keywords and inclusion criteria. Afterwards, the quality of the remaining studies was assessed by using a critical appraisal checklist combined with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 48 publications
4
51
0
2
Order By: Relevance
“…Consequently, LS is expected to impact on teacher learning (Sato et al, 2019), which has been the subject of investigation of several studies (Cheung and Wong, 2014;Coenders and Verhoef, 2018;Vermunt et al, 2019). Most of these studies, however, were small-scale (Cheung and Wong, 2014;Willems and Van den Bossche, 2019) and lacked a clear 'theory of improvement', consequently providing insufficient insight into how and why certain LS elements led to teacher learning (van Veen et al, 2012). Nevertheless, the few studies that did employ a theory-informed research design, with adequate sample sizes, have shown promising results (Willems and Van den Bossche, 2019).…”
Section: Lesson Study and Teacher Professional Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, LS is expected to impact on teacher learning (Sato et al, 2019), which has been the subject of investigation of several studies (Cheung and Wong, 2014;Coenders and Verhoef, 2018;Vermunt et al, 2019). Most of these studies, however, were small-scale (Cheung and Wong, 2014;Willems and Van den Bossche, 2019) and lacked a clear 'theory of improvement', consequently providing insufficient insight into how and why certain LS elements led to teacher learning (van Veen et al, 2012). Nevertheless, the few studies that did employ a theory-informed research design, with adequate sample sizes, have shown promising results (Willems and Van den Bossche, 2019).…”
Section: Lesson Study and Teacher Professional Learningmentioning
confidence: 99%
“…Most of these studies, however, were small-scale (Cheung and Wong, 2014;Willems and Van den Bossche, 2019) and lacked a clear 'theory of improvement', consequently providing insufficient insight into how and why certain LS elements led to teacher learning (van Veen et al, 2012). Nevertheless, the few studies that did employ a theory-informed research design, with adequate sample sizes, have shown promising results (Willems and Van den Bossche, 2019). For example, Schipper et al (2018), in a quasi-experimental study with 48 teachers, found LS to positively impact on feelings of efficacy for inclusive teaching, enhanced classroom management and instruction clarity.…”
Section: Lesson Study and Teacher Professional Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesson study teams have been found to improve teachers' knowledge and skills (e.g. Vermunt et al, 2019;Willems & Van den Bossche, 2019), which in turn can affect student learning (Dudley et al, 2019).…”
Section: Lesson Study Teamsmentioning
confidence: 99%
“…Students should know what to do and how to do it at all times in addition to studying hard. One of the main factors in achieving this is that students should be proficient in effective study strategies and methods (Willems and Bossche, 2019).…”
Section: Introductionmentioning
confidence: 99%